2018
DOI: 10.1107/s1600576718011378
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal space mapping and strain scanning using X-ray diffraction microscopy

Abstract: Dark-field X-ray microscopy is a new full-field imaging technique for nondestructively mapping the structure of deeply embedded crystalline elements in three dimensions. Placing an objective in the diffracted beam generates a magnified projection image of a local volume. By placing a detector in the back focal plane, high-resolution reciprocal space maps are generated for the local volume. Geometrical optics is used to provide analytical expressions for the resolution and range of the reciprocal space maps and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 39 publications
(42 reference statements)
0
43
0
Order By: Relevance
“…Hence, using this simple difference equation we can generate high-resolution q maps. Poulsen et al (2018) also found that the FWHM of the resolution function in the BFP can be ÁQ/|Q 0 | = 4 Â 10 À5 or better in all directions, which is substantially smaller than the angular range of the diffracted beam. We conclude that by placing an aperture in the BFP we can generate a 5D data set.…”
Section: Mapping Dislocations Using An Aperture In the Back Focal Planementioning
confidence: 91%
See 4 more Smart Citations
“…Hence, using this simple difference equation we can generate high-resolution q maps. Poulsen et al (2018) also found that the FWHM of the resolution function in the BFP can be ÁQ/|Q 0 | = 4 Â 10 À5 or better in all directions, which is substantially smaller than the angular range of the diffracted beam. We conclude that by placing an aperture in the BFP we can generate a 5D data set.…”
Section: Mapping Dislocations Using An Aperture In the Back Focal Planementioning
confidence: 91%
“…The intensity distribution in this back focal plane (BFP) is equivalent to the distribution in the Fraunhofer far-field limit. Poulsen et al (2018) present a complementary description of the optical properties of the BFP. Here an alternative approach to mapping the local tilt and local axial strain is provided under the heading of local reciprocal-space mapping.…”
Section: The Dark-field X-ray Microscopy Setupmentioning
confidence: 99%
See 3 more Smart Citations